5'-Monophosphate-activated protein kinase (AMPK) improves autophagic activity in diabetes and diabetic complications - Fan Yao; Ming Zhang; Li Chen (Elsevier, 2016)
Diabetes mellitus (DM), an endocrine disorder, will be one of the leading causes of death world-wide in about two decades. Cellular injuries and disorders of energy metabolism are two key factors in the pathogenesis of diabetes, which also become the important causes for the process of diabetic complications. AMPK is a key enzyme in maintaining metabolic homeostasis and has been implicated in the activation of autophagy in distinct tissues. An increasing number of researchers have confirmed that autophagy is a potential factor to affect or induce diabetes and its complications nowadays, which could remove cytotoxic proteins and dysfunctional organelles. This review will summarize the regulation of autophagy and AMPK in diabetes and its complications, and explore how AMPK stimulates autophagy in different diabetic syndromes. A deeper understanding of the regulation and activity of AMPK in autophagy would enhance its development as a promising therapeutic target for diabetes treatment.